Ketakwaan Sebagai Solusi Krisis Moral Remaja Muslim: Analisis Qs. Ali ‘Imran: 102: Penelitian - Imam Makhrus; Komarudin Sassi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The phenomenon of moral crisis among Muslim youth today has become a serious concern in the fields of education and Islamic outreach. Deviant behaviors such as promiscuity, misuse of social media, and the weakening of values like honesty and responsibility reflect a spiritual vulnerability in the younger generation. This article aims to analyze QS. Ali ‘Imran: 102 through a thematic and educational (tarbawi) tafsir approach in order to explore the concept of taqwa (God-consciousness) as both a preventive and curative solution to the moral crisis facing youth. Using a qualitative approach based on literature review and content analysis of classical and contemporary tafsir works, the study finds that taqwa in this verse is not limited to ritual practices but functions as a mechanism for self-control, strengthening Islamic identity, and developing noble character (akhlaq al-karimah). Taqwa, understood as full awareness of God's presence in every aspect of life, serves as a vital foundation for building moral and spiritual integrity in Muslim youth. This article recommends strengthening the practical application of taqwa through curriculum development, family environment, and social role modeling in order to nurture a generation resilient in both faith and ethics.